KESIAPSIAGAAN KOMUNITAS PESISIR MENGHADAPI ANCAMAN BENCANA GEMPA BUMI DAN TSUNAMI (Studi Kasus di Nagari Tiku Selatan, Kecamatan Tanjung Mutiara, Kabupaten Agam) - Wahyu Hamdika; Alfan Miko; Afrizal Afrizal (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
As a country with high disaster risk, the Indonesian people must prepare and anticipate disasters. The success of the disaster that hit Indonesia confirms that disasters are part of the daily lives of Indonesian people that must be responded wisely. In such conditions, disaster alertness and response also makes efforts to respond to disasters not only limited to curative aspects. This article discusses the ability of coastal communities in their preparedness efforts to face the threat of earthquakes & tsunamis. The communities studied were households that lived along the coast. Using a qualitative research approach, a case study in South Tiku Nagari and using the Theory of Structure of Antony Giddens Duality between agents and structure, this article shows that the ability of coastal communities in their preparedness to face the threat of earthquakes & tsunamis consists of earthquake safety dissemination in homes, bag distribution disaster preparedness, simulation of the tsunami early warning system, earthquake & tsunami simulations, the presence of disaster preparedness savings, increasing evacuation routes regularly, and applying the sister village concept to reduce risk.